PENGUNGKAPAN RISIKO FINANSIAL DAN TATA KELOLA PERUSAHAAN: STUDI EMPIRIS PERBANKAN INDONESIA - Djoko Suhardjanto; Aryane Dewi (University of Merdeka Malang, 2011)
The purpose of this study was to examine the effect of corporate governance to financial risk disclosures ofIndonesian banks. Corporate governance was identified as the board size, the number of board meetings, theproportion of independent commissioners, the proportion of independent audit committee members and numberof audit committee meetings. This study also used leverage and profitability as control variable. The levelof financial risk disclosure was measured based on identified items of a circular enclosure of Bank IndonesiaNo.5/21/DPNP/2003. Under purposive sampling, secondary data of 60 annual reports year 2007-2009 ofbanks in Indonesian Stock Exchange were selected. The average level of financial risk disclosures was at46.50%. It indicated that Indonesians banks were not fully compliance to regulations since financial riskdisclosures were as mandatory matters. The result of multiple regression showed that corporate governanceaffected the level of financial risk disclosure through the variable board size and the number of board meetings.The important role in implementing tata kelola perusahaan(company management) was at the board of commissionerswho served as supervisors of activities and performance of banks as well as advisory directors inensuring that companies implemented good corporate governance, including financial risk disclosures (KomiteNasional Kebijakan Governance, 2006).